Take control of Apple Watch - Carlson, Jeff (Take control., 2022)
Explore everything your Apple Watch can do in watchOS 9! Version 3.0, updated October 21, 2022 Get to know your Apple Watch and customize it to help you focus on what you care about most. Tech expert Jeff Carlson helps you understand the watch mindset, pick the watch model that's right for you, set up and share its faces and their complications, get the notifications you want, take advantage of the health and fitness features, handle communications, and learn how the controls and core apps work. The Apple Watch has become the world's best-selling watch, as well as the most popular wearable digital device. Since the device's introduction in 2015, Apple has developed numerous new watch product lines, vastly expanded the device's capabilities, and enabled developers to create entirely new apps and tools. The Apple Watch hides an enormous amount of technical complexity behind that unassuming touch screen, and with help from author Jeff Carlson, you'll unlock every last bit of its power. Take Control of Apple Watch covers all Apple Watch models through Series 8, the Apple Watch SE (2022), and Apple Watch Ultra, as well as all the new features introduced in watchOS 9. Jeff walks you through getting to know the Apple Watch (including how to pick one out if you haven't already), along with topics that teach you how to navigate among the watch's screens with the physical controls, taps on the screen, and Siri. You'll also find advice on customizing watch faces and sharing them with others; taking advantage of the electrocardiogram (ECG) capability and blood oxygen sensor, plus the temperature sensors introduced in the Series 8 and Ultra; getting the notifications you want; handling text and voice communications; using Apple's core apps; and monitoring your heart rate, hearing, and monthly cycle to improve your overall health. A final chapter discusses taking care of your Apple Watch, including recharging, restarting, resetting, and restoring. Among the many topics covered in the book are: Picking out and setting up your own Apple Watch--covers models up through Series 8, Apple Watch SE (2022), and Apple Watch Ultra Making watch face complications work for you Using the Control Center and Dock Understanding how the watch interacts with your iPhone (including how to control your watch with your iPhone) Staying connected using a cellular-enabled Apple Watch model Using Siri on your watch for a wide variety of tasks Tracking your exercise, even when you leave your iPhone at home Using your watch to monitor sleep data Placing and receiving phone calls on the watch Getting navigation directions (and using the redesigned Compass app, including waypoints and the Backtrack feature introduced in watchOS 9) Using the Walkie-Talkie feature to chat with other Apple Watch owners Sending default (and customized) text messages--and even sending money via Messages Seeing email from only certain people Adding calendar events and reminders Loading your watch with photos and using them to create new watch faces Doing workouts with Apple Fitness+ Finding people, devices, and items Controlling your home with HomeKit-compatible devices Triggering the iPhone's camera remotely using the watch Paying at contactless terminals using Apple Pay Putting tickets on your watch Using health-related features such as the blood oxygen sensor and medication reminders, plus the ECG, Cycle Tracking, and Noise apps Detecting falls and (with newer watch models) car crashes, and automatically calling for help Controlling an Apple TV, or Music on a Mac with the Remote app Unlocking a Mac (and authenticating certain actions) with your watch Adding apps to the watch via your iPhone or the watch's built-in App Store Resetting a messed-up Apple Watch and force-quitting an app.